UnBias: emancipating users against algorithmic biases for a trusted digital economy - Koene, A; Dowthwaite, L; Lane, G; Webb, H; Portillo, V; Jirotka, M (2018)
UnBias is a collaboration between the Horizon Digital Economy Research Institute at the University of Nottingham, the Human Centred Computing group at the University of Oxford and the Centre for Intelligent Systems and their Applications (CISA) at the University of Edinburgh, with creative studio Proboscis. It is funded under the Trust, Identity, Privacy and Security (TIPS) programme of the UK’s Engineering and Physical Sciences Research Council (EPSRC). In this paper we introduce one of our key project outputs; a fairness toolkit which aims to promote awareness and stimulate a public civic dialogue about how algorithms shape online experiences. It will also prompt reflection on possible changes to address issues of online unfairness.